INTRO. RES.#259 - CLEARY, EJ (Tufts Archival Research Center, 2007)
Letter from Edward Cleary of the NY AFL-CIO to Jerry Crispino, the chairman of the New York City Council Health Committee. States opposition to a resolution opposing smoking in public places. Argues that the resolution violates existing negotiated contracts and past practices and that it should be a matter for collective bargaining. Predicts ordinance would lead to divisions in the work force and would decrease productivity.